Social Support and Resilience among People Living with HIV/AIDS in Yogyakarta, Indonesia - Ulfa, Nabilla Dwi; Kusumaningrum, Fitri Ayu (Universitas Islam Indonesia, 2024)
This study explores the relationship between social support and resilience in individuals living with HIV/AIDS. Resilience, defined as the ability to adapt and recover from adversity, is critical for psychological well-being, especially in the face of stigma and discrimination commonly experienced by people with HIV/AIDS. The research aims to determine whether social support significantly contributes to enhancing resilience among this population. The study employed a quantitative approach, involving 64 individuals diagnosed with HIV/AIDS in Yogyakarta, Indonesia. Data were collected using the Multidimensional Scale of Perceived Social Support and the Connor-Davidson Resilience Scale. Statistical analyses, including Pearson’s Product-Moment Correlation and Spearman’s Rho, were conducted to test the hypothesis that higher social support is positively correlated with increased resilience. The findings reveal a significant positive correlation between social support and resilience, with a correlation coefficient of 0.511 and a p-value of 0.000. Resilience levels among participants were generally low, with 81.2% categorized as